Comparison on optimization of star fruit juice using RSM between two Malaysian star fruit varieties (B11 and B10) - Mustapa Kamal, Siti Mazlina; Abdullah, Abdul Ghani Liew; Abd Rahman, Nur Aliaa; Hussain, Siti Aslina; Omar, Rozita (Universiti Putra Malaysia Press, 2008)
In Malaysia, two star fruit varieties, B11 and B10, are planted for commercial purposes. These types of star fruits are suitable for making juices. However, the fresh star fruit juice is cloudy, viscous and green in colour, necessitating the use of enzymes to clarify the juice. Thus, the aim of this study was to establish the optimum conditions for enzymatic treatment of star fruit (B11) juice using response surface methodology (RSM) and to compare the optimum conditions of this variety (B11) with the B10. Star fruit juice (B11) was treated with pectinase enzyme at different enzyme concentrations, incubation times, and temperatures. The effect of this enzymatic treatment was analyzed based on turbidity, clarity, and viscosity. The regression models describing the changes of turbidity, clarity and viscosity were established with the coefficient of determination, R2, which were greater than O.S. The optimum operating conditions for clarifying star fruit juice (B11) was found to be at 0.01 % enzyme concentration at 30 min of incubation time and 30°C of temperature using response surface methodology. The method of treatments for B10 was similar to that of B11. The two varieties of star fruit (B11 and B10) showed different optimum conditions on enzyme concentration and incubation time; however there was no difference in terms of incubation temperature at optimum conditions.